Utilization of Pulsed Electric Field (PEF) Technique in Meat and Seafood Processing - Berkay Kopuk; Recep Güneş; Harun Uran (Turkish Journal of Agriculture: Food Science and Technology)
In the food industry, using of new preservation and processing technologies, which may be an alternative to traditional methods, is becoming increasingly important. These novel and particularly non-thermal techniques have very important advantages such as enhancing food safety, reducing quality losses, and increasing production efficiency. One of these new technologies, Pulsed electric field (PEF) technique, stands out as a novel method that has been emphasized in recent years. It is used for different purposes in both liquid and solid foods, also various studies are carried out for the optimization. On the other hand, recently, there are several studies using PEF technique in meats and seafoods for the preservation purposes, as well as other positive effects (improving the functional properties of the product, accelerating processes such as drying, curing and freezing). In this regard, detailed information about the purposes for which PEF technique can be used in meats and seafoods has been tried to be given in this comprehensive review study.